Etiology and prognosis of nephrocalcinosis according to gestational age in Korean children - Jinwoon Joung; Heeyeon Cho (BMC, 2023)
Abstract Background Nephrocalcinosis (NC) is defined as deposition of calcium in renal tubules and interstitium and is highly related with prematurity and monogenic diseases. Recent studies have reported that NC might be a specific finding of underlying hereditary renal diseases. This study evaluated the risk factors, underlying monogenic causes, and clinical outcomes of NC in Korean children according to gestational age (GA). Methods A total of 464 patients younger than 18 years who were diagnosed with NC by ultrasonography from January 2013 to December 2022 in Samsung Medical Center were enrolled. Medical record data of sex, GA, birth weight, underlying disease, medication history, ultrasonography and genetic analysis were reviewed retrospectively. Results The male to female ratio was 1:0.98, and the mean age at first diagnosis of NC was 385 days. Approximately 62% of patients experienced confirmed resolution of NC after about one year. In comparison of the preterm (mean GA 28 weeks and 2 days) and full-term (mean GA 38 weeks and 2 days) groups, bronchopulmonary dysplasia, patent ductus arteriosus, and use of furosemide and vitamin D were more frequent in the preterm group. In the full-term group, a larger proportion of cases showed persistent NC without resolution and chronic kidney disease (CKD). Genetic analyses were performed in 56 patients, and the monogenic mutation rate was significantly higher in full-term children (OR 10.02, 95% CI [2.464-40.786], p = 0.001). Conclusion While the overall outcomes of pediatric NC are favorable, underlying monogenic causes should be studied, especially in full-term patients without known clinical risk factors.